Optimalisasi Hukum Terhadap Lessee Yang Melakukan Wanprestasi Dalam Perjanjian Leasing - Rianda Dirkareshza; Taupiqqurrahman Taupiqqurrahman; Davilla Prawidya Azaria (Universitas Medan Area, 2021)
This study aims to determine the settlement of default in the leasing agreement where there are steps that must be taken by the lessor, namely giving a summons warning, providing credit policy, to seizing the object of collateral with the help of debt collectors. The ratification of the Supreme Court's Decision Number 18/PUU-XVII/2019 changes the confiscation of the object of collateral which was originally carried out directly, now requires a court process and decision in its execution. This research is a normative juridical law research that is descriptive analytical using a doctrinal legal approach, data collection techniques with data documentation studies and interviews of leasing staff, qualitatively analyzed which discusses law enforcement against Lessees who default and optimizes Lessees who default. The results of the study indicate that the procedures that must be taken by the Lessor first in the process of resolving the Lessee's actions in default are giving a subpoena warning, providing credit policy, to seizing the object of collateral with the help of a third party or debt collector. This is in order to increase effectiveness in the execution of executions and to accommodate the rights of the Lessor as a tax contributor and accelerate the wheels of the nation's economy